Isolation, characterization, and vascular potential of porcine cells in a three-dimensional decellularized liver matrix model - Morini, Sara; Melitón Barbancho, Sandra; Blanes Rodríguez, Álvaro; Pla-Palacín, Iris; Sainz-Arnal, Pilar; Sánchez-Romero, Natalia; Falceto, Maria Victoria; Mitjana, Olga; Romero, Antonio; Del Rio-Nechaevsky, Marcela; Bengochea Martinez, Maria Lourdes; Olmedo Arbizu, Emma; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe bioengineering of solid tissues and organs to mitigate the organ donor shortage has become a critical area of research in tissue engineering and regenerative medicine, where establishing a functional vascular network is crucial, particularly for complex organs such as the lung, kidney, and liver. This requires the isolation and characterization of various vascular cell types. In this quest, pigs have emerged as the preferred experimental animal model in this field, highlighting the importance of procuring and characterizing porcine vascular cells to create organs with functional vasculature for transplant. However, species-unique differences present challenges. Although some of the processes for isolating, expanding, and characterizing porcine vascular cells have been published, these are less established than those for human cells, requiring in our view and experience, additional research. Furthermore, no reliable and comprehensive models currently exist for testing vascular cell interactions in co-culture in vitro.MethodsIn this study, we developed effective methods to isolate and further characterize distinct porcine vascular cell types from various sources. We also introduced a straightforward and practical three-dimensional model for testing vascular cell co-culture, organization and function in vitro.Results and discussionThis proof-of-concept study demonstrates the potential of our co-culture strategy, employing a decellularized liver extracellular matrix disc scaffold microenvironment to assess cell interactions and vascular potential on a small scale in vitro.